Genetically determined telomere length is associated with pancreatic neuroendocrine neoplasms onset - Gentiluomo, Manuel; Capurso, Gabriele; Morelli, Luca; Ermini, Stefano; Pasquali, Claudio; Latiano, Anna; Tavano, Francesca; Greenhalf, William; Milanetto, Anna Caterina; Landi, Stefano; Roth, Susanne; Malecka-Wojciesko, Ewa; et al. (Neuroendocrinology, 2022)
Introduction: Telomere length (TL) is a potential indicator of cancer predisposition; however, the multitude of techniques used to measure it causes the results to be heterogeneous and, in some cases, controversial. In the last years, several studies adopted a strategy based on TL-associated genetic variants to generate a polygenic score, often referred as teloscore, used in lieu of direct TL measurement. For pancreatic neuroendocrine neoplasms (PanNEN), this strategy has not been attempted yet. Methods: A teloscore was generated using 11 SNPs (NAF1-rs7675998, ZNF676-rs409627, TERC-rs10936599, CTC1-rs3027234, PXK-rs6772228, DHX35-rs6028466, OBFC1-rs9420907, ZNF208-rs8105767, ACYP2-rs11125529, TERT-rs2736100, and ZBTB46-rs755017), and 291 PanNEN cases and 1,686 controls collected by the PANcreatic Disease ReseArch (PANDoRA) consortium were genotyped to analyse the association of the teloscore and its individual SNPs with the risk of developing PanNEN. Results: An association between genetically determined long telomeres and the risk of developing PanNEN (OR = 1.99, CI: 1.33–2.98, p = 0.0008) for highest versus median (third) quintile was observed. In addition, two novel SNPs associated with PanNEN risk were identified: ZNF676-rs409627 (ORC/C_vs_G/G = 2.27, CI: 1.58–3.27, p = 8.80 × 10−6) and TERT-rs2736100 (ORC/A_vs_C/C = 2.03, CI: 1.42–2.91, p = 1.06 × 10−4). Conclusion: In conclusion, this study provides for the first time a clear indication of the association between long genetically determined telomeres and increased risk of developing PanNEN.
Gesehen am 01.02.2023